"I expect boredom": Students' experiences and expectations of multiliteracies learning. (28th January 2021) - Lim, Fei Victor; Weninger, Csilla; Nguyen, Thi Thu Ha
Abstract : Multiliteracies has been incorporated in the curriculum of many education systems around the world. Beyond the broadening of focus in literacy to include multimodal meaning‐making, multiliteracies pedagogies are also associated with certain pedagogical shifts, such as a focus on bridging the students' out‐of‐school literacy practices with what and how they are learning in school. This often involves appropriating social media as well as introducing popular culture topics in the classroom. This article discusses the students' perspectives of these ideas to inform the teacher's design of multiliteracies learning. Drawing on data collected through surveys and focus group discussions from a multi‐phased research project on multiliteracies in Singapore, we reflect on the students' expressions of their experiences and expectations on multiliteracies learning. In particular, we surface an instrumental view of learning where concerns over examinations and future career prospects cloud the students' learning. We also identify a desire among the students to keep their worlds of home and schools separate. While the discussion of the students' perspectives is anchored in the context of Singapore, the implications contribute to the global discourse among curriculum planners, educational researchers and teacher practitioners who are interested in improving the design of multiliteracies learning in their contexts.